Analisis Pengaruh Strategi Pemberdayaan Masyarakat Dengan Rekayasa Lingkungan Terhadap Pencegahan Penyakit Diare Di Wilayah Kerja Puskesmas Lubuk Pakam - Gema Mauloni; Mappeaty Nyorong; Asriwati Asriwati (Lembaga Pengembangan Kinerja Dosen, 2023)
Various types of diseases, diarrhea is still dominant in the city of Medan. Based on data from the Central Bureau of Statistics for North Sumatra Province 2017, cases of diarrhea were found to be higher with 10,225 cases compared to other diseases. 5 Of the approximately 2,229,408 total residents of Medan City, it is estimated that 26,025 of them have suffered from diarrhea, this estimate is calculated based on the number national diarrhea morbidity (illness) in 2016, namely 270/1000 population. The estimated number of cases can be used as a target for coverage of cases of diarrhea. The goal to be achieved in this study is to determine the effect of community empowerment strategies in environmental engineering on the prevention of diarrheal diseases in the Lubuk Pakam Health Center area in 2023. The research design used was an analytic survey with a cross-sectional design. The population in this study was 2235 people. This population sample was taken by non-probability sampling or purposive sampling. The number of samples to be studied was 100 people. Data analysis was performed using univariate, bivariate and multivariate analysis. The results of the research on the Advocacy variable obtained p-value = 0.000, Teamwork = 0.001, Communication = 0.002, and Assistance = 0.000 <0.05 meaning that there is an influence between Advocacy, teamwork, communication and assistance on diarrhea prevention. The results of the multivariate analysis were obtained the variable that has the most influence in this study is the mentoring variable with an OR value of 35,174. There is an influence between advocacy, teamwork, communication and assistance on diarrhea prevention. The multivariate analysis results show that the most dominant factor is the assistance variable. It is hoped that the Lubuk Pakam Health Center will further enhance community empowerment in each village in environmental engineering efforts to prevent diarrhea and improve public health status, especially residents who experience diarrhea outbreaks.